Halal Supply Chain Risk Assessment in the Indonesian Beef Supply Chain Using the House of Risk Approach - Irayanti Adriant; Afferdhy Ariffien; Amanda Aryanti (Journal of Digital Marketing and Halal Industry, 2026)
Halal integrity in food supply chains has become increasingly critical due to the complexity of logistics activities and the growing demand for halal-certified products. Existing studies on halal supply chain risk mainly focus on risk identification, with limited attention to operational risk prioritization and proactive mitigation strategies, particularly in local beef supply chains. This research aims to assess halal supply chain risks and determine mitigation priorities in the Indonesian beef supply chain using the House of Risk (HOR) approach integrated with the Supply Chain Operations Reference (SCOR) model and Failure Mode and Effects Analysis (FMEA). Data were collected through in-depth interviews, observations, and expert-based questionnaires involving actors in the beef supply chain. The study identified 17 risk events and 17 risk agents across sourcing, slaughtering, storage, packaging, and distribution activities. The results indicate that the most critical risk agents are poorly trained stunning operators (ARP = 479.66), unhygienic distribution conveyances (ARP = 465.93), and poorly trained slaughter personnel (ARP = 439.89), highlighting the importance of human resource capability and operational hygiene in maintaining halal integrity. The most effective mitigation strategies include training and certification programs, refrigerated transportation systems, and stricter operational compliance procedures. The result extends the application of the HOR framework in halal supply chain risk assessment and provides practical guidance for slaughterhouses and logistics providers in strengthening halal assurance. The study is limited to selected operational actors in the Indonesian beef supply chain.